216k views
5 votes
Find the exact value of the expression.
tan( sin−1 (2/3)− cos−1(1/7))

User Jackytse
by
4.8k points

1 Answer

3 votes

Answer:


\tan(a-b)=(2√(5)-20√(3))/(5+8√(15))

Explanation:

I'm going to use the following identity to help with the difference inside the tangent function there:


\tan(a-b)=(\tan(a)-\tan(b))/(1+\tan(a)\tan(b))

Let
a=\sin^(-1)((2)/(3)).

With some restriction on
a this means:


\sin(a)=(2)/(3)

We need to find
\tan(a).


\sin^2(a)+\cos^2(a)=1 is a Pythagorean Identity I will use to find the cosine value and then I will use that the tangent function is the ratio of sine to cosine.


((2)/(3))^2+\cos^2(a)=1


(4)/(9)+\cos^2(a)=1

Subtract 4/9 on both sides:


\cos^2(a)=(5)/(9)

Take the square root of both sides:


\cos(a)=\pm \sqrt{(5)/(9)}


\cos(a)=\pm (√(5))/(3)

The cosine value is positive because
a is a number between
-(\pi)/(2) and
(\pi)/(2) because that is the restriction on sine inverse.

So we have
\cos(a)=(√(5))/(3).

This means that
\tan(a)=((2)/(3))/((√(5))/(3)).

Multiplying numerator and denominator by 3 gives us:


\tan(a)=(2)/(√(5))

Rationalizing the denominator by multiplying top and bottom by square root of 5 gives us:


\tan(a)=(2√(5))/(5)

Let's continue on to letting
b=\cos^(-1)((1)/(7)).

Let's go ahead and say what the restrictions on
b are.


b is a number in between 0 and
\pi.

So anyways
b=\cos^(-1)((1)/(7)) implies
\cos(b)=(1)/(7).

Let's use the Pythagorean Identity again I mentioned from before to find the sine value of
b.


\cos^2(b)+\sin^2(b)=1


((1)/(7))^2+\sin^2(b)=1


(1)/(49)+\sin^2(b)=1

Subtract 1/49 on both sides:


\sin^2(b)=(48)/(49)

Take the square root of both sides:


\sin(b)=\pm \sqrt{(48)/(49)


\sin(b)=\pm (√(48))/(7)


\sin(b)=\pm (√(16)√(3))/(7)


\sin(b)=\pm (4√(3))/(7)

So since
b is a number between
0 and
\pi, then sine of this value is positive.

This implies:


\sin(b)=(4√(3))/(7)

So
\tan(b)=(\sin(b))/(\cos(b))=((4√(3))/(7))/((1)/(7)).

Multiplying both top and bottom by 7 gives:


(4√(3))/(1)= 4√(3).

Let's put everything back into the first mentioned identity.


\tan(a-b)=(\tan(a)-\tan(b))/(1+\tan(a)\tan(b))


\tan(a-b)=((2√(5))/(5)-4√(3))/(1+(2√(5))/(5)\cdot 4√(3))

Let's clear the mini-fractions by multiply top and bottom by the least common multiple of the denominators of these mini-fractions. That is, we are multiplying top and bottom by 5:


\tan(a-b)=(2 √(5)-20√(3))/(5+2√(5)\cdot 4√(3))


\tan(a-b)=(2√(5)-20√(3))/(5+8√(15))

User Sheilagh
by
4.8k points